Strategi Pemasaran Wisata untuk Meningkatkan Daya Tarik Wisatawan dalam Perspektif Islam - Bahri, Syamsul; Asri, Kholifatul Husna (ALIF: Sharia Economics Journal, 2024)
The focus of this research is the marketing strategy concept carried out by the Papalidan Village tourism manager in Telukpinang village from an Islamic economic perspective. As well as what factors become obstacles in carrying out marketing strategies by Papalidan village tourism managers. The Papalidan tourist attraction is a tourist attraction in Bogor which is located in Teluk Pinang Village, Ciawi District, Bogor Regency. The Papalidan tourist attraction is present in the form of a river (white water rafting). The number of tourists visiting the Papalidan tourist attraction has increased over time after dropping drastically in 2019 due to the pandemic. This research aims to ensure that strategic marketing can rapidly increase tourists visiting the Papalidan tourist attraction. The method used in this research is through questionnaires, observation, library research, documentation and interviews with managers. The data obtained was analyzed using descriptive analysis techniques which were used to analyze the marketing mix and strategy using SWOT analysis and used a Likert Scale to analyze the distributed questionnaires. The results of this research are marketing strategies that can be implemented to increase the number of tourists visiting the Papalidan tourist attraction through branding  Papalidan tourist attraction as a quality natural tourist attraction, maintaining cleanliness and natural beauty, promotion via the internet and brochures to introduce the Papalidan tourist attraction so that it is better known to tourists and image building Papalidan tourist attraction to fix the problems that caused the number of visits in 2019 to drop drastically. Then the following year it started to increase.